Effects of abnormal paddy feeding states on the contact mechanical properties of rubber rollers in rice hullers - Cheng, Min; Zhou, Shihao; Pan, Yong; Meng, Haocong; Wang, Xingchuang; Cao, Xianzhou (International Journal of Agricultural and Biological Engineering, 2026)
Aiming at the problem of uneven wear of rubber rollers in rice hullers, this work systematically revealed the influence mechanism of abnormal paddy flow states on the contact mechanical properties of rubber rollers based on a nonlinear finite element model of the interaction between paddy grains and rubber rollers. The results show that the wear risk of rubber rollers is minimized when the paddy orientation angle ranges from 0° to 15°. At 30°, the contact pressure reaches 12.63 MPa with a sharp increase. At 45°, shear-dominated loading results in a peak von Mises stress of 2.70 MPa, with unsatisfactory rubber roller wear and hulling rate. Paddy orientation angles from 60° to 90° lead to slight rubber roller wear. With a sparse paddy distribution, 3 paddy grains induce shear fatigue in the middle of the rubber roller, whereas 5 grains result in a contact pressure of 7.09 MPa, which can cause local rubber layer detachment. Although 6 paddy grains exhibit the lowest wear risk among sparse distribution conditions, their dynamic stability is poor. Conversely, a dense distribution of 12 paddy grains results in a contact pressure of 6.92 MPa with a time difference of 0.2 ms, featuring a more uniform stress distribution and superior dynamic synchrony. Paddy stacking causes high contact pressure and von Mises stress (up to 13.85 MPa and 5.44 MPa respectively), which is the primary cause of crack initiation and local spalling on rubber rollers. The mechanical performance of stacked paddy flow is far inferior to that of sparsely and densely distributed paddy flows, which will inevitably cause uneven wear of the rubber rollers. This study provides theoretical support for reducing uneven wear of rubber rollers and improving paddy processing efficiency. Key words: rubber roll huller, uneven wear, abnormal paddy flow, nonlinear finite element, contact pressure, von Mises stress DOI: 10.25165/j.ijabe.20261901.10272 Citation: Cheng M, Zhou S H, Pan Y, Meng H C, Wang X C, Cao X Z. Effects of abnormal paddy feeding states on the contact mechanical properties of rubber rollers in rice hullers. Int J Agric & Biol Eng, 2026; 19(1): 251–262.